Architectural and symbolic value of the Central Pavilion of the National University of Engineering - Salazar Briones, Sandra (2019)
This article identifies the symbolic and architectural value of the Central Pavilion. The first building built for the National Engineering University in its new premises. The methodology applied in this research is drawn through the analysis of the urban and historical context, the study of the architectural typologies and the new construction materials that made this work one of the most modern of its time. Through the collection of images and information, the role it has acquired in society from its origin to the present will be known. The objective of this study aims to contribute to the sociocultural dissemination of the emblematic building of the UNI and evaluate the state of its current conservation.